THE ROLE OF HARMONY IN THE WORKPLACE TO IMPROVE ENTREPRENEURIAL PERFORMANCE: MEDIATING ROLE OF HUMAN RESOURCE AMBIDEXTERITY - Saleh Mahdi Mohammed Al-Hasnawi; Bushra Mohammed Alwan; Ruaa Salih Mahdi; Ahmed Abdullah Amanah (Scholars Digest Publishing, 2024)
The research aimed to analyze and understand the relationship between the independent variable, harmony in the workplace with its dimensions (cooperation, teamwork, and goal achievement) and the dependent variable, entrepreneurial performance with its dimensions (creativity, risk-taking, and proactiveness) through the mediating role of human resources management ambidexterity with its dimensions (exploring opportunities and investing in opportunities). The problem was represented by the following question: (What is the relationship between harmony in the workplace and achieving entrepreneurial performance through the mediator of human resources management ambidexterity at the University of Kerbala?) The importance was clarified through the findings that were obtained from a survey of the opinions of the research sample represented by (90) respondents. Of the directors of the University of Kerbala as a community, amounting to (120) directors, by adopting a questionnaire form prepared according to a five-point Likert scale. Descriptive statistical methods were used, including the arithmetic mean and standard deviation, as well as analytical statistical methods, including linear regression and the correlation coefficient using the statistical program (SPSS) and the (Sobel) test for the significance of the mediating role. A set of conclusions were obtained, the most prominent of which was the effectiveness of the mediating role of human resource ambidexterity in enhancing the relationship between harmony in the workplace and entrepreneurial performance at the University of Kerbala and the research community.
Keywords: Harmony In Workplace, Human Resource Ambidexterity, Entrepreneurial Performance, University of Kerbala, Iraq.